Mapping of proximal enamel thickness in permanent teeth - Flávio Vellini Ferreira; Flávio Augusto Cotrim Ferreira; José Alaor Ribeiro; Rívea Inês Ferreira Santos (Universidade Estadual de Campinas, 2015)
Aim: Knowledge of enamel thickness is relevant to perform stripping during orthodontic treatment. Thus, proximal enamel measurements of human permanent teeth were compared in this study. Methods: The measurements were previously obtained on cut sections of mandibular central (n = 30) and lateral (n = 30) incisors, canines (n = 20), first (n = 40) and second (n = 40) premolars; maxillary central (n = 20) and lateral (n = 20) incisors, canines (n = 20), first (n = 40) and second (n = 42) premolars. Comparisons between thicknesses by arch side and proximal surface were carried out using Student's t-tests (α = 0.05). Teeth were compared according to the mesial and distal thicknesses by ANOVA and Tukey's test. Results: No significant differences were found between right and left teeth. For the mesial surface, the mandibular second premolar presented the highest mean value (1.376 mm ± 0.198; p<0.001). The mandibular central incisor had the smallest thickness in relation to the other teeth (0.675 mm ± 0.144), although not significant compared with the mandibular lateral incisor and canine (0.734-0.781 mm). The mandibular second premolar also presented the higher distal thickness in relation to the others (1.450 mm ± 0.172), although not significant compared with the maxillary first premolar (1.322 mm ± 0.195). Mandibular incisors had the lowest means for distal thickness (0.872-0.879 mm), although not statistically different compared with maxillary incisors and mandibular canine (1.002-1.015 mm). Distal thickness was greater than mesial (p<0.001). Conclusions: Interproximal stripping should be less marked in incisors and mesial surfaces.